Interfiguralität bei Phaedrus Ein fabelhafter Fall von Selbstinszenierung - Park, Johannes (Millennium-Studien / Millennium Studies, 2017)
In the prologues and epilogues to his Fables, Phaedrus - despite the low reputation of the genre - develops a complex if at times inconsistent poetics. The ambivalences and contradictory nature of his poetics are part of the fabulist`s self-presentation, whereby certain figures, such as Aesop the trickster, the donkey, and even divine figures such as Prometheus play central role.